PEMIKIRAN MUHAMMAD SYAHRUR TENTANG KEWARISAN KALÂLAH DAN RELEVANSINYA TERHADAP PEMBARUAN HUKUM ISLAM - Arham, Akbaru Wustho; Elfia, Elfia (Jurnal AL-AHKAM, 2020)
This  study  aims  to  analyze  Muhammad  Syahrur's  thoughts  about  the  inheritance of kalâlah and compare with the opinion of the ulema's jumhur 'and their relevance to the renewal of Islamic law.  This research is a normative legal research or library research using secondary data.  The results of this study revealed that: first, Syahrur  interpreted  kalālah  with  someone  who  died  but  did  not  have  children,  both boys  and  girls  and  did  not  have  grandchildren,  male  or  female,  and  did  not  have  a father  or  mother  and  grandfather  or  grandmother.    Secondly,  in  the  case  of  the application  of  the  distribution  of  the  inheritance  of  kalâlah  obtained  by  the  heirs, Syahrur  distinguishes  the  method  of  the  distribution  of  kalālah  assets  in  two conditions,  namely  the  first  and  the  second  kalālah  conditions.    Third,  Syahrur's thoughts  on  the  inheritance  of  kalálah  cannot  be  categorized  as  renewal  in  Islamic law  because  there  is  already  a  thought  that  is  almost  simultaneously  with  the  pre- existing  scholars  namely  Hazairin,  one  of  Indonesian  Islamic  jurists  who  adheres  to the concept of bilateral inheritance, especially regarding the inheritance of kalálah.  Keywords: Muhammad Syahrur, kalâlah inheritance, renewal of Islamic law.